Role Of Innovations In Economic Development - Abdushukurova Sevinch Akramjonovna (Peerian Journals Publishing, 2024)
This article provides ideas about the possibility of rapid development of entrepreneurship through the wide use of innovations in the modern world.
Keywords: Innovation; Innovationinnovative process; production factors